2019
DOI: 10.1093/toxsci/kfz142
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease-Related Serum Proteins in Workers Occupationally Exposed to Polycyclic Aromatic Hydrocarbons

Abstract: Chimney sweeps have higher incidence and mortality of cardiovascular disease (CVD), likely related to their exposure to polycyclic aromatic hydrocarbons (PAH). In order to identify underlying mechanisms of PAH-related CVD, we here investigated whether PAH exposure was associated with levels of putative CVD-related proteins in serum among currently working chimney sweeps. We enrolled 116 chimney sweeps and 125 unexposed controls, all nonsmoking male workers from Sweden. We measured monohydroxylated PAH metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Similarly, chimney sweeps, who are occupationally exposed to particulate matter and PAHs, were reported to have CVD-related proteins [protein-glutamine gamma-glutamyltransferase 2 (TGM2), glyoxalase I (GLO1), NF-kappa-B essential modulator (NEMO), follistatin (FS), prointerleukin-16 (IL-16), and heat shock protein beta-1 (HSP 27)] in their sera. These serum protein markers also showed a positive association with the monohydroxylated metabolites of PAHs ( 173 ). Some of these proteins were correlated with homocysteine and cholesterol.…”
Section: Developments In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, chimney sweeps, who are occupationally exposed to particulate matter and PAHs, were reported to have CVD-related proteins [protein-glutamine gamma-glutamyltransferase 2 (TGM2), glyoxalase I (GLO1), NF-kappa-B essential modulator (NEMO), follistatin (FS), prointerleukin-16 (IL-16), and heat shock protein beta-1 (HSP 27)] in their sera. These serum protein markers also showed a positive association with the monohydroxylated metabolites of PAHs ( 173 ). Some of these proteins were correlated with homocysteine and cholesterol.…”
Section: Developments In the Fieldmentioning
confidence: 99%
“…Exposure to PAHs also may have induced oxidative stress in chimney sweeps, which could lead to endothelial dysfunction and inflammation resulting in atherosclerosis and hypertension (175). The increased expression of GLO1, NEMO, FS, and HSP 27 in chimney sweeps could be a compensatory response against PAH-induced oxidative damage (173).…”
Section: Relevance Of Proteomics In Chemical Exposure-induced Cvdmentioning
confidence: 99%
“…PEA has been successfully used to detect plasma biomarkers for cancer and cardiovascular diseases. [26][27][28] According to both manufacturers, more than 80% of the assays are expected to detect proteins on ethylenediaminetetraacetic acid-treated plasma from healthy donors. In our study, using the PEA platform, 79.7% of the assays were able to detect proteins in at least 25% of the vitreous samples, whereas only 41.5% of the ECL assays detected proteins in more than 25% of the vitreous samples.…”
Section: Discussionmentioning
confidence: 99%
“…PEA has been successfully used to detect plasma biomarkers for cancer and cardiovascular diseases. 26 28 …”
Section: Discussionmentioning
confidence: 99%
“…In another study, the authors found that PAH exposure was associated with levels of putative cardiovascular disease-related proteins in serum. The findings show that differentially expressed proteins are mainly involved in inflammatory response and immunological functions, such as leukocyte migration, leukocyte cell movement, and immune cell adhesion [38]. In addition, some PAHs metabolites also show consistent positive association with C-reactive protein, a plasma inflammation marker [39].…”
Section: Discussionmentioning
confidence: 99%